Over frequency control of photovoltaic inverters in an island microgrid. (January 2019) - Hsu, Cheng-Ting; Cheng, Tsun-Jen; Huang, Hung-Ming; Lee, Yih-Der; Chang, Yung-Ruei; Jiang, Jheng-Lun
Abstract: This paper discusses the power variation of photovoltaic power plant (PVPP) impact on the frequency response of an isolated island microgrid. An island microgrid with PVPPs and diesel generators is selected for study. The power system network, diesel generation units, load and PVPP data are collected in detail. And the one-line diagram of the study system with regarding peak and off-peak loading is set up in the simulation software for the steady state load flow analysis. After that, the transient stability analysis is executed with considering the tripping and power variation of various PVPP ramp rates with and without considering the over frequency compensation of photovoltaic (PV) inverters. The dynamic response of diesel generators and system frequency are examined carefully. It is found that the over frequency phenomenon can be controlled effectively by the regulation of PV inverters to achieve better reliability of the microgrid.